2013
DOI: 10.4254/wjh.v5.i11.612
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus reactivation with rituximab-containing regimen

Abstract: Rituximab is recognized as a useful drug for the treatment of B-cell non-Hodgkin's lymphoma and its use has been extended to such diseases as idiopathic thrombocytopenic purpura, thrombotic thrombocytopenic purpura, chronic rheumatoid arthritis and AN-CA-associated vasculitides. One serious complication associated with its use is the reactivation of hepatitis B virus and the search for methods to prevent this occurrence has resulted in the rapid accumulation of knowledge. In this review, we discuss case analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 75 publications
0
40
1
1
Order By: Relevance
“…Reactivation of HBV could be either spontaneous or due to intensive chemotherapy or immunosuppressive therapy [10,11], immune restoration after highly active antiretroviral therapy for HIV [12,13], treatment-related [14], or reactivation of the occult HBV infection by rituximab (anti-CD20)-based chemotherapy [15][16][17]. Similarly, reactivation of Hepatitis C virus infection has also been reported, especially after immune suppressive therapy [18,19].…”
Section: What Constitutes An Acute Insultmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactivation of HBV could be either spontaneous or due to intensive chemotherapy or immunosuppressive therapy [10,11], immune restoration after highly active antiretroviral therapy for HIV [12,13], treatment-related [14], or reactivation of the occult HBV infection by rituximab (anti-CD20)-based chemotherapy [15][16][17]. Similarly, reactivation of Hepatitis C virus infection has also been reported, especially after immune suppressive therapy [18,19].…”
Section: What Constitutes An Acute Insultmentioning
confidence: 99%
“…Acute hepatic insults of infectious etiology included reactivation of Hepatitis B virus (HBV) as the leading cause of ACLF in the Asian region [10][11][12][13][14][15][16][17][18][19]. Reactivation of HBV could be either spontaneous or due to intensive chemotherapy or immunosuppressive therapy [10,11], immune restoration after highly active antiretroviral therapy for HIV [12,13], treatment-related [14], or reactivation of the occult HBV infection by rituximab (anti-CD20)-based chemotherapy [15][16][17].…”
Section: What Constitutes An Acute Insultmentioning
confidence: 99%
“…For instance, rituximab, is an agent predominantly used to treat haematological malignancy in addition to autoimmune and neurological disease. 9,10 Rituximab is an agent that works against CD20 on B-cell. CD20 positive B-cells depletion might reduce the number of CD4 memory cells, CD8 cells, and antibody-mediated immunity.…”
Section: Chemotherapeutic Agents Associated With Hepatitis B Virus Rementioning
confidence: 99%
“…The rate of hepatitis B virus reactivation during rituximab treatment when combined with chemotherapy has been reported to be 20-55% overall and 3% in patients with negative HbsAg. 10,11 due to various chemotherapeutic/ immunosuppressive agents are shown in Table 2 and Figure 3.…”
Section: Chemotherapeutic Agents Associated With Hepatitis B Virus Rementioning
confidence: 99%
“…No studies have been reported focussing upon CVID patients infected with hepatitis C through means other than immunoglobulin exposure, although a case study in the era prior to IVIg suggested that rapid and severe disease can occur after natural infection with hepatitis B virus . Furthermore, hepatitis B reactivation and infection severity has been shown to be significantly increased in those treated with Rituximab, an agent which targets antibody production via CD20 B cells; however, it is unclear if there is a significantly increased mortality . In prevalence studies completed in the wake of contaminated blood products, there was not a significant number of asymptomatic patients carrying viral hepatitis viruses .…”
Section: Hepacivirusesmentioning
confidence: 99%